Mewujudkan Kesadaran Energi Melalui Konsep Khalifah Fi al-’Ard - Muhamad Iqbal (JURNAL PENELITIAN, 2016)
This paper discusses the concept of khalifah fil arḍ as God’s representative in preserving nature. It aims to build awareness of energy derived from natural resources. This research is a library-based study using a qualitative descriptive approach. Based on the analysis of the data, the study concludes that comprehensive knowledge of energy awareness forms the foundation of the concept of khalifah fil arḍ. Promoting energy awareness within society therefore represents a contemporary manifestation of the role of khalifah fil arḍ.